Determinants of academic staff readiness for the adoption of online teaching-learning platforms in African universities during COVID-19 pandemic (2021)
Effective teaching-learning activities require considerable preparation in terms of knowledge of the content, pedagogical skills and provision of relevant instructional materials. The proliferation of Information and Communication Technology (1CT) and its adoption for teaching raised issues on the expected level of ICT efficacy, needed by lecturers for effective use of modem technologies for teaching. This situation was fueled by the advent of COVID-19 pandemic which warranted institutions at all levels to adopt online/remote teaching-learning platforms as the alternative means of continue education activities while learners are still at home due to the social distance policy. Using remote platforms has raised questions about its effectiveness as there was no prior training for lecturers and how their personal characteristics would promote the adoption of remote platforms have not been established. This creates impetus to examine institutional readiness determinants using staff personal characteristics as a test case. Ex post facto design was adopted for the study. The population comprised lecturers from Higher institutions who responded to an online questionnaire using "Google forms" (research instrument) titled Higher Institutions Academic Staffs Readiness (H1ASR, r=0.91) from which 173 lecturers from higher institution in Africa were purposively selected. Data collected were analysed, using Ordinary Least Square regression and O-probit at 0.05 level of significance. Results revealed that joint contributions of independent variables (gender, academic cadre and self-efficacy) was significant (R(2)=0.204, F-test=3.475. p<0.05); staff academic cadre (β= -2.295, t=-1.88, p<0.05) and self-efficacy (β= -1.914, t=2.00, p<0.05) made significant contributions but no significant contribution was made by gender (β= -.426, t= -1.17, p>0.05). It is recommended that external factors such as, internet facilities and bandwidth, alongside academic staffs personal characteristics, should he given high level of consideration.